2018
DOI: 10.1093/conphys/coy031
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a blubber-based endocrine pregnancy test for humpback whales

Abstract: There are few identifiable external indicators of pregnancy state in live baleen whales. However, progesterone can be quantified from biopsy samples that are collected from free-ranging whales. We use a blubber sample archive and associated calving data from a well-studied population to develop a blubber-based pregnancy test for humpback whales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 43 publications
2
58
2
Order By: Relevance
“… Logistic model used to assign the probability of pregnancy in humpback whales sampled along the WAP. Model was previously described in Pallin et al [ 51 ]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Logistic model used to assign the probability of pregnancy in humpback whales sampled along the WAP. Model was previously described in Pallin et al [ 51 ]. …”
Section: Resultsmentioning
confidence: 99%
“…Pregnancy was assigned using the methods developed by Pallin et al [ 51 ]. Briefly, we used the progesterone concentrations from a collection of female humpback whales of known pregnancy status, based on annual calving observations, to develop a predictive model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blubber has become a widely used sample matrix for reproductive and stress assessments of both odontocete (for examples see: Kellar et al , 2006 , Kellar et al ., 2009 , Trego et al , 2013 , Kellar et al , 2015 , Trana et al , 2016 , Champagne et al , 2018 ), and mysticete whales (e.g. Mansour et al , 2002 , Kellar et al , 2013 , Vu et al , 2015 , Mello et al , 2017 , Pallin et al , 2018 , Carone et al , 2019 , Atkinson et al , 2020 ). For instance, pregnant females can be readily identified using blubber progesterone concentrations in several whale species ( Mansour et al , 2002 , Kellar et al , 2013 , Pallin et al , 2018 , Inoue et al ., 2019 , Atkinson et al , 2020 ), and blubber cortisol measurements have shown promise for assessing human impacts ( Kellar et al , 2015 ) and environmental stressors ( Trana et al , 2016 ) on cetaceans.…”
Section: Introductionmentioning
confidence: 99%
“…Blubber samples from whales can be obtained by biopsy sampling and therefore measuring the level of progesterone in blubber has the potential to investigate the reproductive status in free-ranging cetacean species. For example, Pallin et al (2018) used blubber biopsy samples for assigning pregnancy in humpback whales Megaptera novaeangliae. It is expected that the application and development of such non-lethal methods will increase in the future.…”
Section: Introductionmentioning
confidence: 99%